Acute Rhabdomyolysis in a Child with Multiple Suspicious Gene Variants - Aiko Murakami; Rhiana L. Lau; Robert Wallerstein; Tamara Zagustin; Garett Kuwada; Prashant J. Purohit (Hindawi Limited, 2022)
Rhabdomyolysis is diagnosed with creatinine kinase (CK) elevation beyond 1000 U/L or ten times above the normal upper limit. Severe episodes can be fatal from electrolyte imbalance, acute renal failure, and disseminated intravascular coagulation. A 13-month-old child was admitted with a CK of 82,090 U/L in the setting of respiratory tract infection-related hyperthermia of 106.9° farenheit. His medical history was significant for prematurity, dystonia, and recurrent rhabdomyolysis. His home medications clonazepam, clonidine, and baclofen were continued upon admission. He exhibited uncontrolled dystonia despite treatment for dystonia. Therefore, sedative infusions and forced alkaline diuresis were begun to prevent heme pigment-induced renal injury. Despite these interventions, his CK peaked at 145,920 U/L, which is rarely reported in this age group. The patient also developed pulmonary edema despite diuresis and required mechanical ventilation. Sedative infusions were not enough for dystonia management, and he needed the addition of a neuromuscular blocking infusion. He finally responded to these interventions, and the CK normalized after a month. He required a month of mechanical ventilation and two and a half months of hospitalization and extensive rehabilitation. We were able to avert renal replacement therapy despite pulmonary edema and an estimated glomerular filtration rate nadir of 21 mL/min/1.73 m2 based on the bedside Schwartz formula. He made a complete recovery and was discharged home. His growth and development were satisfactory for two years after that event. His extensive diagnostic workup was negative. Unfortunately, he died from septic and cardiogenic shock with mild rhabdomyolysis two years later. Prompt recognition, early institution of appropriate therapies, identification of underlying disease, and triggering events are pivotal in rhabdomyolysis management. Evidence-based guidelines are needed in this context.